PERSEPSI MASYARAKAT TERHADAP CLEAN GOVERNANCE DI PROVINSI GORONTALO - Fitroy Ishak (Publik : (Jurnal Ilmu Administrasi), 2015)
Realizing good governance is not only a public expectations but also the demands of contemporary governance. This study aims to determine the public perception of "clean governance" in the province of Gorontalo. This study uses a qualitative method. Making informant is purposive and snowball. Data were collected through observation, interview, and review documents. Data analysis using data reduction, data presentation, and conclusion and verification. The results showed that the overall governance in Gorontalo province is not in accordance with the paradigm of “clean governance". Specifically, the citizens consider matters related to information, public services, social assistance, and recruitment is still decorated with the practice of "bad governance" that leads to corruption, collusion and nepotism